Efeito da época de adubacão nitrogenada em cobertura na producão e qualidade fisiológica de sementes de ervilha (Pisum sativum L) - de Souza Romero, Nilton Carlos [UNESP]; Haga, Kuniko Iwamoto [UNESP]; Orioli Junior, Valdeci [UNESP]; Cardoso, Eliana Duarte [UNESP] (Soc Chilena Ciência Suelo, 2008)
An important factor in crop production is the nutrient liberation matching the growth rates, so these combined effects together with plant development can reach the best results. In this work, the times of nitrogen application (topdressing) were tested in the rate of 120 kg ha(-1) of N, applied at 20 (T20), 25 (T25), 30 (T30), 35 (T35) and 40 (T40) days after emergency in eight cultivars of pea (Pisum sativum L) (Maria, Kodama, Mikado, Flavia, Luiza, Amelia, Dileta and Marina). Here, the aim was to evaluate the effect of these treatments on yield and seed quality in Cerrado Region. After harvest, the seeds were submitted to the quality tests (germination tests, electric conductivity and emergency under field conditions). The results showed that the peas crops are not influenced by the N timing application. Amongst the eight cultivars studied, the best productivity were for Mariana, Mikado, Amelia, Maria and Flavia and the lowest yield was for Kodama cultivar. The cultivar Mikado showed the best results for the quality tests.
Timing efect of broadcast nitrogen fertilization on the producction and physiological quality of pea seeds (Pisum sativum L)
Keywords: Pisum sativum L.; nitrogen; times of application; seeds quality